Menggali Kepemimpinan Pendidikan yang Efektif: Integrasi Pendekatan Transformasional dan Transaksional dalam Era Merdeka Belajar - Sigiyuwanta, Recsatasha (Universitas Negeri Malang, 2024)
Abstract Educational leadership becomes increasingly important in the era of Merdeka Belajar, where the dynamics of education continue to change and develop. The era of Merdeka Belajar opens a new space for the transformation of educational leadership in Indonesia. In this context, transformational and transactional approaches have become the main focus in understanding the essence of effective educational leadership. However, the integration of these two approaches still requires further exploration. This research aims to understand the essence of effective educational leadership through the integration of transformational and transactional approaches in the era of Merdeka Belajar. Using the literature study method, this article delves into related literature to explore the concepts of transformational and transactional leadership, and to identify possible integrations between them. The results of the analysis show that the integration of transformational and transactional approaches in educational leadership can create a more holistic and adaptive leadership model. This integration allows educational leaders to combine the inspirational and motivational elements of transformational leadership with the tactical and administrative aspects of transactional leadership. The transformational approach focuses on vision, inspiration, and empowerment, while the transactional approach emphasizes clarity of expectations and consequences. Through a review of literature and empirical studies, this article illustrates the strategies and practices required for educational leaders to build inclusive learning environments, motivate staff and students, increase organizational commitment and performance, and sustainably improve academic outcomes. The findings highlight the importance of leaders' adaptability in responding to the demands of constant change in today's educational development. Abstrak Kepemimpinan pendidikan menjadi semakin penting di era Merdeka Belajar, di mana dinamika pendidikan terus berubah dan berkembang. Era Merdeka Belajar membuka ruang baru bagi transformasi kepemimpinan pendidikan di Indonesia. Dalam konteks ini, pendekatan transformasional dan transaksional telah menjadi fokus utama dalam memahami esensi kepemimpinan pendidikan yang efektif. Namun, integrasi kedua pendekatan ini masih memerlukan eksplorasi lebih lanjut. Penelitian ini bertujuan untuk memahami esensi kepemimpinan pendidikan yang efektif melalui integrasi pendekatan transformasional dan transaksional dalam era Merdeka Belajar. Dengan menggunakan metode studi pustaka, artikel ini menggali literatur terkait untuk mengeksplorasi konsep kepemimpinan transformasional dan transaksional, serta untuk mengidentifikasi kemungkinan integrasi di antara keduanya. Hasil analisis menunjukkan bahwa integrasi pendekatan transformasional dan transaksional dalam kepemimpinan pendidikan dapat menciptakan model kepemimpinan yang lebih holistik dan adaptif. Integrasi ini memungkinkan pemimpin pendidikan untuk menggabungkan elemen-elemen inspirasional dan motivasional dari kepemimpinan transformasional dengan aspek-aspek taktis dan administratif dari kepemimpinan transaksional.